Tabletop magnetic resonance elastography for the measurement of viscoelastic parameters of small tissue samples - Ipek-Ugay, Selcan; Driessle, Toni; Ledwig, Michael; Hirsch, Sebastian; Braun, Juergen; Sack, Ingolf; Guo, Jing (Journal of Magnetic Resonance, 2015)
We demonstrate the feasibility of low-cost tabletop MR elastography (MRE) for quantifying the complex shear modulus G of small soft biological tissue samples as provided by pathologists. The MRE system was developed based on a tabletop MRI scanner equipped with a 0.5 T permanent magnet and a tissue sample holder mounted to a loudspeaker. A spin echo sequence was enhanced with motion-encoding gradients of 250 mT/m amplitude synchronized to acoustic vibration frequencies. Shear wave images suitable for elastography were acquired between vibration frequencies of 0.5 and 1 kHz in agarose, ultrasound gel, porcine liver, porcine skeletal muscle, and bovine heart with a spatial resolution of 234 μm pixel edge length. The measured frequency dependence of G agreed well with previous work based on high-field MR systems. The ratio between loss and storage moduli was highest in liver and ultrasound gel, followed by muscle tissue and agarose gel while ultrasound gel and liver showed similarly low storage moduli compared to the other samples. The shear wave to noise ratio is an important imaging criteria for MRE and was about 4.2 times lower for the preliminary setup of the 0.5 T tabletop system compared to a 7 T animal scanner. In the future, the new tabletop MRE system may serve as a low cost device for preclinical research on the correlation of viscoelastic parameters with histopathology of biological samples.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Complex shear modulus; Heart; Liver; Muscle; Soft biological tissue; Tabletop magnetic resonance elastography; Tissue samples; Viscoelastic parameters